(untitled) (Scientific journal of the Fergana State University, 2025)
The article investigates lyrical poems which depict World War II together with its tragic aftermaths. The introduction examines how the problem evolved along with an evaluation of existing literature. This part of the work identifies the studied literature together with its analysis methods while discussing relevant scientific concepts which play a role in the composition. The desired scientific data has been obtained. The main section explores how war and its sickness appear within the lyrics of Khurshid Davron together with those of Eshkobil Shukur